Pulse Interval Optimization for Doppler Ambiguity Clutter Suppression in Missile-Borne STAP Radar - Shi, Jieming; Cheng, Ziyang; Li, Jun; He, Xuan; Li, Huiyong (IEEE geoscience and remote sensing letters, 2024)
Doppler ambiguity in missile-borne radar is usually caused by the low pulse-repetition-frequency (PRF) waveforms, which may result in a significant performance loss of target detection and location in the presence of clutter. To solve the issue of Doppler ambiguity clutter in missile-borne space-time adaptive processing (STAP) radar, this letter proposes a novel clutter suppression approach with the aid of designing the pulse interval (PI) of the waveform. Specifically, we formulate the optimization problem by considering the metric of minimizing the maximum sidelobe level in the Doppler domain, subject to the constraint of a given coherent processing interval (CPI). To solve the complicated problem, the modified genetic algorithm combining the simulated annealing algorithm (MGA-SA) is devised. Extensive simulations showcase that the proposed method surpasses SCNR by over 3 dB in clutter suppression effectiveness when compared to conventional techniques, all while maintaining the same dwell time and frequency resources.